An Lp theory of sparse graph convergence II: LD convergence, quotients, and right convergence - Borgs, Christian; Chayes, Jennifer; Cohn, Henry; Zhao, Yufei (2014)
We extend the Lp theory of sparse graph limits, which was introduced in a companion paper, by analyzing diff erent notions of convergence. Under suitable restrictions on node weights, we prove the equivalence of metric convergence, quotient convergence, microcanonical ground state energy convergence, microcanonical free energy convergence, and large deviation convergence. Our theorems extend the broad applicability of dense graph convergence to all sparse graphs with unbounded average degree, while the proofs require new techniques based on uniform upper regularity. Examples to which our theory applies include stochastic block models, power law graphs, and sparse versions of W-random graphs.